Advanced Topics in Multimedia Research - Deb, Sagarmay (IntechOpen, 2012)
As multimedia has become a very important technology, significantly improving people's lives, this book provides an up-to-date scenario of various fields of research being carried out in the area. The book covers topics including web-based co-operative learning, effective distance learning through multimedia, quality control of multimedia on the internet, recovery of damaged images, Network-on-Chip (NoC) as a global communication vehicle, and Network GPS for road conditions (such as traffic and checkpoints). We believe that the book will help researchers in the field to proceed further in their research on multimedia.